Evaluation of native isolates of Nomuraea rileyi for the control of Spodoptera frugiperda (Lepidoptera: Noctuidae) - BOSA-O., CARLOS FELIPE; CHÁVEZ, DORA; TORRES, LISSETTE; PARÍS, ALEJANDRO; VILLAMIZAR, LAURA; COTES, ALBA MARINA (Revista Colombiana de Entomología, 2004)
The fall armyworm, Spodoptera frugiperda, is the major insect pest of the maize crop. Considering that the country does not have a registered product based on fungal entomopathogens for the control of S. frugiperda, and given that Nomuraea rileyi is a microorganism that is most frequently found to cause epizootics in the fleld. our objective was to isolate and select strains of this fungus with high biocontrol activity against S. frugiperda. To do this, the biocontrol activity of 10 isolates of N. rileyi, isolated under laboratory conditions from the Llanos Orientales, at 1x107 conidia.ml-1 was evaluated by spraying onto "higuerilla" leaves (Ricinus communisi infested with second instar larvae. A mortality of 94, 7, 95 and 100% were obtained with three isolates, the isolate Nm-07 from Villavicencio being selected because it caused 100% mortality and the lowest lethal times (LT50 and LT90) of 6, 2 and 7,9 days, respectively. Afterwards, both the lethal concentrations and doses of this isolate were determined with LC50 of 9,8 x 10’ conidia.ml-1 at 11 days and LC90 of 2,2 x 105 conldla.ml-1 at eight days. respectively. To determine the lethal doses 5 µ1 of N. rileyi suspensions were applied to the thoracic tergum of each larvae, with a LD50 of 44 conidia/larvae after 12 days and a LD90 of 3,380 conidia/larvae after 10 days, respectively. These results offer reference parameters to conduct studies on mass production and formulation directed towards the integrated control of Spodoptera spp.